Estimation and Forecasting of HPG's Return Rate in Vietnam Using The ARIMA-GARCH Model - Phung Duy, Quang; Tong, Phuong Mai; Nguyen, Nhat Minh; Nguyen Thi, Mai Linh; Chu Thi, Loan; Vu Thi, Cam Anh (Journal of Applied Statistics and Data Science, 2025)
The volatility of stock indices in the stock market is a crucial basis for market evaluation and trend prediction, often having a significant impact on investment and trading decisions. Therefore, analyzing and forecasting these changes helps to effectively manage risk and optimize returns for investors. This study analyzes the volatility of the return rate of HPG stock based on its closing prices from 24/09/2021 to 24/09/2024. The most suitable model selected for forecasting is ARIMA(11,0,19)-GARCH(1,1). The results indicate that, between 25/09/2024 and 04/10/2024, the return rate of HPG stock is expected to experience slight fluctuations with varying positive and negative returns. However, the decline is not significant and does not substantially affect the long-term trend of the stock.